Pelatihan Pembelajaran Menulis Cerita Bergambar Berbasis Ethno-Pedagogy untuk Meningkatkan Literasi Siswa dan Mendukung SDGs-4 - Wardhani, Prayuningtyas Angger; Yarmi, Gusti; Sari, Yofita (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
In order to improve student literacy, the author proposes community service in the form of teacher assistance in teaching picture story writing. This community service will be held at primary schools in the Garut Regency. This activity aims to provide solutions to partner schools that have problems with health literacy and environmental awareness. With this community service activity, teachers can implement a programme that is integrated with eco-pedagogy appropriately so as to improve students' health literacy. The results of the activity showed enthusiasm and an average evaluation score of 88.55%. These results indicate that the community service activity has been successful. Translated with DeepL.com (free version)